Early administration of magnesium sulfate and its impact on clinical outcomes in ICU-admitted patients with COPD: a retrospective cohort study - Xiao, Min; Chen, Min; Ding, Xuefeng; Lin, Shan (Frontiers in Pharmacology, 2025)
BackgroundMagnesium sulfate is commonly utilized in critical care due to its vasodilatory, bronchodilatory, and neuroprotective properties. However, its impact on mortality outcomes in patients with chronic obstructive pulmonary disease (COPD) requiring intensive care remains inadequately defined.MethodsA retrospective cohort study was conducted on patients with COPD who were admitted to the ICU at Beth Israel Deaconess Medical Center in Boston from 2008 to 2019. Early administration of magnesium sulfate was considered for intravenous administration within 48 h of ICU admission. Propensity-score-based methods, such as inverse probability weighting, were employed to evaluate the correlation between early use of magnesium sulfate and 28-day mortality.ResultsA total of 3,651 ICU admissions for COPD were included, of which 1,148 (31.4%) patients received magnesium sulfate within the first 48 h. Administering magnesium sulfate early was linked to a reduced 28-day mortality rate (hazard ratio 0.76, 95% confidence interval 0.60–0.95), with consistent results across predefined subgroups. This correlation remained consistent regardless of baseline serum magnesium levels and did not increase the risk of acute kidney injury (AKI). The calculated E-value of 1.96 indicates that significant unmeasured confounding factors would be necessary to fully account for the observed relationship.ConclusionIn this single-center retrospective cohort, early magnesium sulfate administration in critically ill patients with COPD was associated with lower 28-day mortality without an observed increase in AKI risk. These results advocate for prospective multicenter studies to validate these connections, investigate optimal dosing approaches, and pinpoint the patient subgroups most likely to benefit from this intervention.